Peripherally inserted central catheters in critically ill patients – complications and its prevention: A review - Sona Duwadi; Qinghua Zhao; Birendra Singh Budal (International Journal of Nursing Sciences, 2019)
Peripherally inserted central catheter (PICC) is extensively used in critical care settings, because it plays a vital role in providing safe central venous entry. However, PICC is associated with several complications, which should be detected to shorten the duration of patients’ improvement, reduce health care cost, and lessen the incidence of various PICC-related complications. Therefore, this study aimed to outline current literature on PICC procedures, potential complications, and measures for prevention. Understanding evidence-based guidelines regarding insertion technique, early detection of complications, and care bundle of PICC is significant in complication prevention. Implementation of education, training, and appropriate multidisciplinary approaches on PICC care among nurses and caregivers is the key to preventing complications. Thus, the strict care of indwelling PICC lines, the targeted and reasonable PICC-associated complication prevention, and nursing care have a major clinical significance in reducing the occurrence of potential PICC complications. Keywords: Catheterization, Central venous, Complications, Intensive care, Patients, Prevention strategies, Review